Determinants of Profitability in Indonesian Islamic Banks: Insights on Financial Performance - Humairah, Nadia; Andriansyah, Yuli; Badjie, Fatou (Unisia, 2023)
This study examines the factors influencing profitability in Islamic banks in Indonesia, focusing on leverage, firm size, capital adequacy, and liquidity. As Islamic banks operate under Sharia principles that emphasize ethical financial practices and risk-sharing, understanding these determinants is crucial for enhancing financial performance while adhering to regulatory and ethical standards. The study aims to provide insights into how these financial metrics interact to shape profitability, as measured by Return on Assets (ROA). A quantitative research approach was employed, utilizing secondary data from Islamic banks operating between 2007 and 2018. Multiple regression analysis was conducted to assess the relationships between the independent variables—leverage, firm size, capital adequacy, and liquidity—and the dependent variable, ROA. Diagnostic tests were performed to ensure the validity and reliability of the model. The results reveal that leverage and liquidity positively and significantly impact profitability, highlighting their roles in operational expansion and financial stability. Conversely, firm size has a significant negative effect, suggesting that larger institutions face operational inefficiencies. Capital adequacy, while essential for stability, does not directly influence profitability, indicating potential underutilization of capital. These findings align with and extend prior research, emphasizing the unique dynamics of Islamic banking. This study contributes to the understanding of Islamic finance by offering empirical evidence specific to Indonesia, a major market for this sector. The findings underscore the need for efficient resource allocation, robust liquidity management, and strategies to address inefficiencies in larger banks. These insights provide valuable guidance for practitioners and policymakers aiming to optimize financial performance in Islamic banking.